Cyanide inhibition and pyruvate-induced recovery of cytochrome c oxidase - Nůsková, Hana; Vrbacký, Marek; Drahota, Zdeněk; Houštěk, Josef (Journal of bioenergetics and biomembranes, 2010)
The mechanism of cyanide's inhibitory effect on the mitochondrial cytochrome c oxidase (COX) as well as the conditions for its recovery have not yet been fully explained. We investigated three parameters of COX function, namely electron transport (oxygen consumption), proton transport (mitochondrial membrane potential Δψ(m)) and the enzyme affinity to oxygen (p₅₀ value) with regard to the inhibition by KCN and its reversal by pyruvate. 250 μM KCN completely inhibited both the electron and proton transport function of COX. The inhibition was reversible as demonstrated by washing of mitochondria. The addition of 60 mM pyruvate induced the maximal recovery of both parameters to 60-80% of the original values. When using low KCN concentrations of up to 5 μM, we observed a profound, 30-fold decrease of COX affinity for oxygen. Again, this decrease was completely reversed by washing mitochondria while pyruvate induced only a partial, yet significant recovery of oxygen affinity. Our results demonstrate that the inhibition of COX by cyanide is reversible and that the potential of pyruvate as a cyanide poisoning antidote is limited. Importantly, we also showed that the COX affinity for oxygen is the most sensitive indicator of cyanide toxic effects.
Keywords: Potassium Cyanide; Liver; kyselina pyrohroznová; Rats; játra; Electron Transport; mitochondrie; Electron Transport Complex IV; spotřeba kyslíku; Oxygen Consumption; Rats, Wistar; mužské pohlaví; membránový potenciál mitochondrií; krysa rodu Rattus; kyanid draselný; transport elektronů; kyslík; Pyruvic Acid; zvířata; protony; Mitochondria; Protons; potkani Wistar; Oxygen; Membrane Potential, Mitochondrial; respirační komplex IV; Male; Animals